Ionic Liquids New Aspects for the Future - Kadokawa, Jun-ichi (IntechOpen, 2013)
Concerns with ionic liquids are one of the most interesting and rapidly developing areas in modern physical chemistry, materials science, technologies, and engineering. Increasing attention has also been paid to the use of ionic liquids in the research fields of biological aspects and natural resources. This book provides the forum for dissemination and exchange of up-to-date scientific information on theoretical, generic, and applied areas of ionic liquids. It, therefore, tends to review recent progresses in ionic liquid research on fundamental properties, solvents and catalysts in organic reactions, biological applications, providing energies and fuels, biomass conversions, functional materials, and other applications. I trust that this book will provide an active source of information for research in ionic liquid science and engineering.